A formação inicial em educação física para a inclusão em escolas - SILVA, Jéssica Freitas (2020)
The present study deals with na analysis of the initial training in physical education for the inclusive scholastic work of students, and has as a lócus of research and data collection the Federal University of Pará. The objectives proposed were to analyze the training of the academic graduates of the Federal University of Pará from the Physical Education course for inclusive school performance, to identify the understanding of these academics regarding the qualification to work with inclusion and to point out the importance of the disciplines that approach Inclusive Physical Education. For this, dialogues were established with authors Who discuss this área after a bibliographical research, as well as historical contextualizations about inclusion and physical education. This study was based on qualitative research, a questionnaire was applied, data analysis and comparisons with the literature and PPP of the course. We show at the end of this research and in discussions that it is necessary debates, problematizations that lead to contributions for the development of na initial formation that qualifies the future professor of physical education to work in an inclusive way in the school context.